2021
DOI: 10.1177/10497323211061340
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Not Really a Part of Standard Practice’: Institutional Silencing of Sexuality Within Australian Mental Health Settings

Abstract: Research seeking to understand and improve sexuality-related practice in mental health settings has paid little attention to the institutional context in which clinicians’ practice is embedded. Through a social constructionist lens, we used thematic analysis to examine how 22 Australian mental health clinicians implicated the wider institutional context when discussing and making sense of sexuality-related silence within their work. Interviews were part of a study exploring participants’ perceptions of sexuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Structural barriers to communication about sex and intimacy were frequent, consistent with previous research in this and other fields of medicine and nursing (Salehian et al 2017;Karani and McLuskey 2020;Urry et al 2022). Insufficient time and privacy, generic, out-dated or inappropriate resources, the lack of a protocol, and a lack of training were all obstacles.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Structural barriers to communication about sex and intimacy were frequent, consistent with previous research in this and other fields of medicine and nursing (Salehian et al 2017;Karani and McLuskey 2020;Urry et al 2022). Insufficient time and privacy, generic, out-dated or inappropriate resources, the lack of a protocol, and a lack of training were all obstacles.…”
Section: Discussionsupporting
confidence: 78%
“…Significant barriers to Australian health professionals providing the level of recommended care (Levine et al 2012;Steinke et al 2013) were identified. Australian clinicians are wrestling with similar barriers to effective communication as health professionals in other countries, and in other health care settings (Annerstedt and Glasdam 2019;O'Connor et al 2019;Karani and McLuskey 2020;Urry et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings challenge the common emphasis in wider literature on a need for individual‐focused interventions including education. The problem of inadequate sexuality‐related care in mental health settings is embedded in the broader contexts where clinicians work and must therefore be addressed through that broader context (see Urry, In press). The insufficiency of educational interventions alone to achieve ‘service transformation’ has been acknowledged by researchers working to address other challenges in mental healthcare delivery (see McCloughen & Buus, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sexuality and sexual health are challenging and complex areas of care within health and mental settings (Hughes et al, 2018). Within recovery‐oriented mental health care contexts, and in alignment with the World Health Organization (2015) working definitions, these are best understood as holistic and affirmative concepts that incorporate a range of domains including, but necessarily extending beyond , concerns related to physical illness, physical function, and reproduction (see Urry, In press). A holistic approach is also aligned with the reported experiences and needs of individuals engaging in mental health services (e.g., Evans et al, 2021; McCann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%